Configurações do trabalho do assistente social na atenção primária em saúde (APS) no século XXI : um estudo da produção teórica do serviço social brasileiro - Camargo, Marisa (2014)
The work of social workers in primary care of the Unified Health System (UHS) is the central theme of this Doctoral Thesis in Social Work, which main goal was to explain the job settings of the social worker in Primary Health Care (PHC) in theoretical yield of Social Service, in order to unravel the interface of professional ethical-political project and the care in the Unified Health System (UHS) in the twenty-first century style. To this end, we resorted to the literature search, the explanatory type, with a qualitative approach, theoretical and epistemological framework based on the critical dialectical method of inspiration and its theoretical and methodological categories historicity, totality, contradiction and mediation articulated to the themes of social work assistant, professional ethical-political project of Social Service, Primary Health Care (PHC), the Unified Health System (UHS) and the model of care in health, inspired by the theoretical framework of Social Work and Public Health and publications and measures of the Ministry of Health (MOH). The twenty publications of Social Service about the work of social workers in primary care of the Unified Health System (UHS) in the period from 2005 to 2012, located in the bibliographical sources for collecting survey data were subjected to content analysis with themed cut. The results at the end of the spiral work process research show that, according to the incipient theoretical yield of Social Service, the work of social workers in primary care of the Unified Health System (UHS) in the XXI century is configured as merges the interface between professional ethical-political project of social work, with different models of care conformed within the Unified Health System (UHS) and the polysemy of theoretical-conceptual and technical-operative approaches to primary health care (PHC), in tension between the recognition of determinants or health needs as a social right of state responsibility in view of the completeness and the commodification of health in the form of goods restricted to the dictates of neoliberal capitalist society project, hegemonic on the contemporary scene.